Perlindungan Hukum Terhadap Bumdes Simpan Pinjam dalam Perkara Kredit Macet yang Disebabkan Adanya Wanprestasi oleh Debitur di Desa Kesimpar Karangasem - I Putu Utama Putra; I Nyoman Putu Budiartha; I Wayan Arthanaya (Jurnal Interpretasi Hukum, 2021)
Village-owned enterprises are mostly owned by the village through direct participation originating from the wealth of the village itself. The purpose of establishing a village-owned enterprise is to create job vacancies for the community and as a result increase the income of the village itself. Of course, in establishing BUMdes, you must follow the procedures as they are regulated in the village law. This study aims to examine the legal protection of BUMdes savings and loans against bad credit cases in Kesimpar Village and reveal the settlement of bad loans in BUMdes Kesimpar Village. This study uses empirical legal research and the problem approach used is the legislative and conceptual approach. The sources of data used are primary data, namely interviews with related parties and secondary data including legislation. Data were collected by means of interviews obtained with informants in the BUMdes Panca Datu, Kesimpar Village. Furthermore, the data were analyzed qualitatively and then concluded inductively. The results of the study reveal that the legal protection of BUMdes savings and loans in the case of bad loans caused by default by debtors in Kesimpar Karangasem Village is holding on to the agreement letter and legal protection for BUMdes is regulated in Bali Governor Regulation Number 44 of 2017, Law of the Republic of Indonesia Number 10 1998, Law Number 4 of 1996 and efforts to settle bad loans at BUMDES Panca Datu through repressive means.